#### Answer

$$y = \frac{{12}}{5} + C{e^{ - 5x}}$$

#### Work Step by Step

$$\eqalign{
& \frac{{dy}}{{dx}} + 5y = 12 \cr
& {\text{this equation is already written in the form }}\frac{{dy}}{{dx}} + P\left( x \right)y = Q\left( x \right) \cr
& {\text{comparing }}\frac{{dy}}{{dx}} + 5y = 12{\text{ with }}\frac{{dy}}{{dx}} + P\left( x \right)y = Q\left( x \right){\text{ we can note that }}P\left( x \right){\text{ is 5 }} \cr
& {\text{The integrating factor is }}I\left( x \right) = {e^{\int {P\left( x \right)} dx}} \cr
& I\left( x \right) = {e^{\int {P\left( x \right)} dx}} = {e^{\int 5 dx}} = {e^{5x}} \cr
& {\text{multiplying both sides of the differential equation by }}{e^x} \cr
& {e^{5x}}\frac{{dy}}{{dx}} + 5{e^{5x}}y = 12{e^{5x}} \cr
& {\text{Write the terms on the left in the form }}{D_x}\left[ {I\left( x \right)y} \right] \cr
& {D_x}\left[ {{e^{5x}}y} \right] = 12{e^{5x}} \cr
& {\text{solve for }}y{\text{ integrating both sides}} \cr
& {e^{5x}}y = \int {12{e^{5x}}} dx \cr
& {e^{5x}}y = 12\left( {\frac{{{e^{5x}}}}{5}} \right) + C \cr
& {e^{5x}}y = \frac{{12{e^{5x}}}}{5} + C \cr
& y = \frac{{12}}{5} + \frac{C}{{{e^{5x}}}} \cr
& {\text{or}} \cr
& y = \frac{{12}}{5} + C{e^{ - 5x}} \cr} $$